176k views
5 votes
1.........................simplify

1.........................simplify-example-1
User Hft
by
5.2k points

2 Answers

2 votes

Answer:

22 - 8√5

Explanation:

(2√5 - 4)(3√5 + 2)

= 2√5(3√5 + 2) - 4(3√5 + 2)

= 6√(5×5) + 4√5 - 12√5 - 8

= 6√25 + 4√5 - 12√5 - 8

=6×5 + 4√5 - 12√5 - 8

=30 - 8 + 4√5 - 12√5

= 22 - 8√5

User Martiert
by
5.7k points
7 votes

Answer:


22-8√(5)

Explanation:

Since all the answer choices arent visible, i will directly give the answer.

We will use the distributive property in expanding, which is
(a+b)(c+d)=ac+ad+bc+bd

So we have:


(2√(5)-4 )(3√(5) +2)\\=(2√(5))(3√(5) )+2(2√(5) )-4(3√(5) )-4(2)\\=6√(5) √(5)+4√(5)-12√(5)-8\\=6(5)+4√(5)-12√(5)-8\\=30+4√(5)-12√(5)-8\\=22-8√(5)

Note: we have used the radical property
√(a)√(a)=a here

User WGH
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.